A subnational affordability assessment of nutritious foods for complementary feeding in Kenya - Theresa Ryckman; Patrick Codjia; Stella Nordhagen; Caroline Arimi; Veronica Kirogo; Laura Kiige; Penjani Kamudoni; Ty Beal (Wiley, 2024)
Abstract Complementary feeding among children aged 6-23 months is a key determinant of micronutrient deficiencies and childhood stunting, the burdens of which remain high in Kenya. This study examines the affordability of complementary foods to increase young children's nutrient consumption across eight provinces in Kenya. We combined data from household surveys, food composition tables and published sources to estimate the cost of portion sizes that could meet half of the children's daily iron, vitamin A, calcium, zinc, folate, vitamin B12 and protein requirements from complementary feeding. These costs were compared to current household food expenditures. The selection of foods and price and expenditure data were stratified by province. Our analysis indicates that vitamin A, vitamin B12 and folate are affordable to most households in Kenya via liver, beans and in some provinces, orange‐fleshed fruits and vegetables, avocado and small dried fish. Calcium, animal‐source protein, zinc and iron were less affordable and there was more provincial variation. In some provinces, small dried fish were an affordable source of calcium, protein and zinc. In others (North Eastern, Central, Eastern, parts of Rift Valley and Coast), small dried fish were not commonly consumed and other foods were less affordable. Future research should consider interventions aimed at reducing prices, increasing availability and changing behaviours related to these foods. Solutions such as supplementation and fortification may be needed for iron and zinc in some locations. Food affordability presented the greatest barriers in North Eastern province, which had lower dietary diversity and may require additional targeted interventions.